Supervisory control and data acquisition system (SCADA) based customized remote terminal unit (RTU) for distribution automation system - Musse, Mohamud Ahmed; Soo, Wai Lian (2008)
This paper presents the development of a supervisory control and data acquisition (SCADA) based remote terminal unit (RTU) for customer side distribution automation system (DAS). It is to apply automation technique for operating and controlling low voltage (LV) down stream of 415/240 V. The SCADA system developed provides fault isolation operation, monitoring and controlling functions for the operators and data collection for future analysis. An embedded Ethernet controller is used as RTU to act as converter for human machine interface (HMI) and to interact with digital input and output modules. RTU is the master and digital input and output modules are the slaves. RTU will initiate the transaction with the digital input and output modules. Two proprietary software systems are used are to develop algorithm for the controller and to develop HMI for monitoring and controlling functions for the operator.